A 17‐element conodont apparatus from the Soom Shale Lagerstätte (Upper Ordovician), South Africa. (13th March 2013) - ALDRIDGE, RICHARD J.; MURDOCK, DUNCAN J. E.; GABBOTT, SARAH E.; THERON, JOHANNES N.
<x xml:space="preserve">Abstract</x> Abstract: Natural assemblages of a new conodont taxon, Notiodella keblon, from the Upper Ordovician Soom Shale Lagerstätte of South Africa contain 17 elements. This is the first time that a 17‐element apparatus plan has been unequivocally demonstrated in conodonts. The apparatus comprises paired P1, P2, P3, M, S1, S2, S3 and S4 elements and an unpaired, axial S0 element and provides a new template for use in the reconstruction of apparatuses from the collections of dispersed elements, particularly for those with icrion‐bearing P1 elements and perhaps for other balognathids.